Some Criticisms of Sufism and their Answers - Said Ghulam Mohammad Hashmi; Salahuddin Momand; Seraj Ahmad Habibi (Randwick International of Education and Linguistics Science Journal, 2023)
If philosophy, on one hand, has so many followers and believers, on the other hand, it has critics and opponents. The ones who criticize are usually mullahs and slightly educated ones. They assume that Sufis’ acts and views do not have any place in Islamic Sharia. The acts and views which are criticized by them are the raqs (dance) and sama (singing), going to shrines and considering it a way of being close to Allah and of accepting prayer, respecting their Pirs and Murshids to the rank of worship, giving a special dhikr to his murids and specifying a special number to it by the Pir, and etc. This article is written in the light of holy Islamic Sharia aiming to answer such criticisms and objections, so they also reach the true and original reality based on it. The contents and conclusion of this article prove that various criticisms and objections, which they have against Sufism, have no base and origin of Islamic Sharia. In fact, the source of the mentioned criticisms and objections comes from personal complexes and beliefs. Therefore, this article tries to analyze and clarify this issue in the light of first hand references of Islamic Sharia, so they take the message that the evidence that they try to use as proof, the Sufi and theosophist also use it as proof; however, the only difference is that they and the Sufis draw different conclusions from it. Researching this issue is important because people are going away from the spirituality and coming closer to materiality at this time and they should not do this because love with materiality causes the destruction of life in the world and the hereafter. This is a library research and its method is analytical and descriptive.